The Problem of Unemployment among Higher Degrees' Holders at the Algerian University: A Sociological Study of Causes and Implications - ZAKIA LAMRAOUI; NORA TAMRABET (Social Empowerment Journal, 2020)
This study aimed to investigate the problem of unemployment among holders of higher degrees at the Algerian university by identifying the causes of this problem and reveal the reflections that can mimic it on the individual and society. In addition to trying to develop, a set of solutions to reduce unemployment rates among the category concerned with the research. We used a descriptive approach and a questionnaire; it was distributed to 217 individuals.We have concluded that the gap between training outputs in higher education and the requirements of the labor market due to the focus on qualitative lack of scientific value, in addition to the decline of value systems in the university institution and the presence of violations at the level of various organizational practices, the so-called tragedy of the elite in Algerian society has resulted, this reflected negatively on the degree of self-esteem of individuals and thus the desire to search for other external affiliation capable of investing in their cognitive competencies.